Chapter La Russia sovietica con gli occhi dei viaggiatori fascisti: frattura come (parziale) integrazione - Farsetti, Alessandro (Biblioteca di Studi Slavistici, 2017)
Thanks to a linguistic comparison of travel notes by Fascist intellectuals in the USSR I have identified three interpretative models of the Soviet phenomenon: theories about the character of Russian people; the presence of analogies between Soviet industry and American Fordism; similarities between fascism and communism. The result is both a fracture and integration with the West: as a fracture, Soviet Russia was perceived as positively close to Fascist Italy, whereas the similarities with the American model of economic growth were considered negative.